Serum BUN and creatinine estimation in patients of overt hypothyroidism: a case control study - Kumari, Bandana; Kumar, Pawan; Keshari, Jiut R.; Kumar, Arun; Pankaj, Sangeeta; Chaudhary, Radha K. P. (International Journal of Research in Medical Sciences, 2017)
Background: Hypothyroidism or underactive thyroid or low thyroid is a common endocrine disorder characterized by low serum T3 (triiodothyronine), T4 (thyroxine) and raised TSH (thyroid stimulating hormone). Thyroid hormones are involved in renal development and hemodynamic, kidney structure and GFR (glomerular filtration rate). Aim of this study was to see the alteration of basic renal markers in patients of hypothyroidism. Methods: A total of seventy subjects were included in the study. Thirty-five were patients of hypothyroidism and thirty-five were age and sex matched normal controls. Serum T3, T4, TSH, creatinine and BUN (blood urea nitrogen) were estimated in both groups. Results: Serum T3, T4 were significantly decreased and TSH was significantly raised among cases as compared to controls. Mean value of serum creatinine and BUN were within normal range in both the groups but these values were significantly raised among cases as compared to controls with p value 0.02 and 0.003 respectively. Also, there was positive correlation of TSH with BUN and creatinine among cases.